Diper Överlöde - Kinney, Jeff (Kinney, Jeff. Diary of a wimpy kid (Series), 2022)
Greg Heffley goes on tour with his brother Rodrick and Roderick's band Diper Överlöde hoping to experience the glamorous rock lifestyle. However, Greg soon learns being on tour means money problems, inter-band fighting, and lots of thankless late nights. Though Greg is determined to help the band succeed, the realities of life on the road threaten to sink them.